Increasing Science Learning Motivation in Elementary Schools: Innovation with Interactive Learning Videos Based on Problem Based Learning - Citra Wibawa, I Made; Ni Wayan Rati; Basilius Redan Werang; Jian-Bang Deng (Universitas Negeri Semarang, 2024)
The problem found in fourth grade is that the learning process tends to only use the lecture method so that students are not motivated to learn because it tends to be boring. In addition, the use of learning media is not optimal. This development research has objectives, namely to: (1) describe the design of PBL-based interactive learning video media, (2) find out the acceptability of PBL-based interactive learning video media, (3) find out the effectiveness of the application of PBL-based interactive learning video media used to increase IPAS learning motivation of grade IV elementary school students. This development research uses the ADDIE model, there are five stages, namely: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. Data collection method with document study and questionnaire. The instrument used to collect data is a questionnaire guideline. The effectiveness of the model was tested through an experiment involving control and experimental groups, where pre-tests and post-tests were used to measure differences in student learning motivation before and after the application of learning media. The results showed that: (1) this study has succeeded in producing PBL-based interactive learning video media that ensures a more interactive and engaging learning experience, particularly suited for fostering problem-solving skills in science education of grade IV elementary school students. (2) media acceptability validation index of 0.944 with very high predicate / qualification; (3) the significance value (2-tailed) in the correlated t-test shows a number of <0.001, smaller than 0.05 (significance level of 5%). In conclusion PBL-based interactive learning video media is effectively used to increase IPAS learning motivation of grade IV elementary school students.